Cover Feature: Alcohol Synthesis from CO2, H2, and Olefins over Alkali‐Promoted Au Catalysts—A Catalytic and In situ FTIR Spectroscopic Study (ChemSusChem 3/2019). Issue 3 (1st February 2019) - Heyl, Denise; Kreyenschulte, Carsten; Kondratenko, Vita A.; Bentrup, Ursula; Kondratenko, Evgenii V.; Brückner, Angelika
Abstract : The Cover Feature shows the direct synthesis of 1‐propanol from CO2, H2, and ethene. This process includes two steps: the hydrogenation of CO2 to CO by reverse water‐gas shift reaction and subsequent hyroformylation of ethene with the formed CO and hydrogen. Gold nanoparticles together with alkali dopants are responsible for reactant activation. More information can be found in the Full Paper by Heyl et al. onpage 651 in Issue 3, 2019 (DOI:10.1002/cssc.201801937 ).